Asthma increases short-time sickness absence and presenteeism in young adults - Inger Kull, RN, PhD; Maria Ödling, RN, PhD; Ida Mogensen, MD, PhD; Anne-Sophie Merritt, PhD; Theo Bodin, MD, PhD; Gun Johansson, PhD; Sandra Ekström, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: There is limited knowledge on how asthma affects short-term sickness absence and presenteeism among young adults. Objective: Our aim was to investigate associations between asthma and short-term sickness absence and presenteeism among young adults. A secondary aim was to investigate the influence of comorbidity with rhinitis and skill levels in occupations for these associations. Methods: The study included 2029 participants from the population-based Barn/Children Allergy Milieu Stockholm Epidemiology (BAMSE) cohort who answered questions on allergic disease at age 24 years and questions on work-related outcomes in a follow-up at age 28 years. Short-term sickness absence was defined as sickness absence lasting fewer than 14 days. Presenteeism was defined as working despite being unwell. Analyses were performed with multinominal logistic regression (sickness absence) and logistic regression (presenteeism) adjusted for sex, education, employment status, smoking status, and body mass index. Results: The participants with current asthma reported more short-term sickness absence and presenteeism, respectively, than did those without current asthma (eg, 37.2% vs 30.5% reported 2-4 episodes and 8.6% vs 5.7% reported ≥5 episodes in the preceding 12 months [P = .01]). In multivariate analyses, current asthma was associated with frequent sickness absence (relative risk ratio = 1.37 [95% CI = 1.02-1.84 for 2-4 episodes] and relative risk ratio = 1.74 [95% CI = 1.03-2.94 for ≥5 episodes]), as well as higher presenteeism (odds ratio = 1.40 [95% CI = 1.06-1.85]). For the most frequent sickness absence category (≥5 episodes), there was an association for asthma with, but not without, allergic rhinitis and a tendency for a greater association in occupations with low- versus high-skill levels. Conclusion: Asthma is associated with frequent short-term sickness absence and presenteeism among young adults. Optimal treatment and management of asthma may reduce its negative consequences on working life.